Ghosts. - Ibsen, Henrik, 1828-1906.; Nazimova, 1879-1945.; Chaney, Stewart; Ibsen, Henrik, 1828-1906.; National Theatre Corporation (Washington, D.C.); Richard L. Coe Theater Programs Collection (Library of Congress) (1936., 1936)
National Theatre, direction, Rapley Theatre Corporation, S.E. Cochran, manager, Nazimova in Henrik Ibsen$1 (Bs "Ghosts," directed by Mme. Nazimova, production designed by Stewart Chaney.s
National Theatre, week beginning May 4, 1936, matinees Wednesday and Saturday.
"Playgoer, the magazine of the theatre. Vol. 7. May 4 to May 9l, 1936. No. 23"--p. 3.
Title devised by Library staff.
Cast: Beatrice de Neergaard, Raymond O$1 (BBrien, McKay Morris, Mme. Nazimova, Harry Ellerbe.s
In: Richard L. Coe Theater Programs Collection (Library of Congress).
LC copy accompanied by errata sheet with cast change for Horace Sinclair in the role of Jacob Engstrand.
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1936.